OPC UA support for Beremiz softPLC - Martim Afonso Maia Henriques da Silva (2018)
Integration of the Industrial Automation protocol OPC UA in the IEC 61131-3 compliant Beremiz softPLC. The mapping between IEC 61131-3 elements and OPC UA will follow the "OPC UA Information Model for IEC 61131-3" specification.